First Molecular Detection of Pathogens Leptospira in Common Rodent Captured in North Algeria Urban Areas - Lila Lekhal; Elena Harran; Anaïs Aragon; Karine Groud; Marine Le Guyader; Rachid Kaidi; Djamel Khelef; Zouheira Djelouadji (Tropical Medicine and Infectious Disease, 2022)
Leptospirosis is an anthropozoonosis disease of worldwide distribution caused by mobile spirochetes of the genus Leptospira and rodents, mainly rats, are described as its primary reservoir. In Algeria, there is limited data about the prevalence of Leptospira spp. in humans and animals, as well as Leptospira carriage in wild rodents. The study aimed to highlight the importance of rodents as a reservoir of Leptospira bacterium in Blida city in Algeria by detecting and identifying circulating Leptospira species in the rodent population. A total of 101 rodents, 95 Rattus Norvegicus, 5 Rattus Rattus, and 1 Mus Musculus were captured and tested for pathogenic Leptospira spp. byreal-time PCR targeting the Leptospira 16S rRNA (rrs) gene, revealing a total prevalence of 40.6%, 95% IC [30.9–50.8%]. Positive samples were subjected to species-specific real-time PCR assays targeting L. interrogans, L. noguchii, L. borgpetersenii, and L. kirschneri for species identification. However, positive samples for which Leptospira-species could not be determined were subjected to conventional PCR targeting the partial 16S rRNA (rrs) gene, and amplified DNA was subjected to sequencing. Leptospira spp. was detected in 36 kidney, 16 urine, and three lung specimens. L. interrogans was identified in 39 rodents and L. borpetersenii in one rodent; however, one rodent with renal carriage could not be typed due to poor DNA quality. This study provides the first description of pathogenic Leptospira spp. in wild rodents in Algeria. These findings suggest a high potential risk of leptospirosis transmission from rodents to humans and animals in Algeria and therefore imply the adoption of prophylactic measures. In addition, further studies, including different animals and rodent species, should be conducted to clarify the epidemiology of this disease in Algeria.